1972
DOI: 10.3171/jns.1972.37.5.0562
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous malformations of the brain

Abstract: ✓ The quality of survival of 150 patients with arteriovenous malformations of the brain is presented. The mean period of follow-up was over 15 years. The surgically operated and conservatively managed groups are compared, a comparison that in the long run appears to favor the operated cases. The results are discussed and indications for surgery summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
1
5

Year Published

1980
1980
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(86 citation statements)
references
References 12 publications
3
77
1
5
Order By: Relevance
“…3,26 After initial hemorrhage, rebleeding rates have been reported to vary between 6% and 18% per year. 7,9,11,14,31 In 315 patients with AVMs who were referred for radiosurgery, Pollock et al 31 found an annual hemorrhage rate prior to SRS of 1.89% in patients who had not suffered a previous hemorrhage, compared with an annual risk of 7.45% in patients who had suffered one or more hemorrhages (p < 0.001).…”
mentioning
confidence: 99%
“…3,26 After initial hemorrhage, rebleeding rates have been reported to vary between 6% and 18% per year. 7,9,11,14,31 In 315 patients with AVMs who were referred for radiosurgery, Pollock et al 31 found an annual hemorrhage rate prior to SRS of 1.89% in patients who had not suffered a previous hemorrhage, compared with an annual risk of 7.45% in patients who had suffered one or more hemorrhages (p < 0.001).…”
mentioning
confidence: 99%
“…Tras la primera hemorragia, hay una mortalidad del 10-30% y una morbilidad grave del 10-20% 2,6,13,30,33,35 . Sobre la recurrencia del sangrado, numerosos artículos muestran una recurrencia de hemorragia del 6 al 18% al año 5,9,11,13,35 . Todo ello depende de las características de la MAV en la que tendremos en cuenta como factores predictores de sangrado más significativos: la hemorragia previa, la presencia de aneurismas intranidales (según Redekop G 37 , el riesgo de hemorragia con aneurisma intranidal es del 9,8%) y el drenaje venoso profundo 3,5,16,37 .…”
Section: Discussionunclassified
“…Partial excision/obliteration of AVMs or DAVFs does not offer protection against future hemorrhage risk and, in many reports, increases the risk of hemorrhage in the postoperative period. 26,27,34,35 Various surgical techniques, including packing of the sinus, skeletonization of the sinus, disconnection of the feeders, as well as disconnection of the leptomeningeal venous drainage, have been described. [9][10][11]13,[36][37][38][39][40] Although it has been mentioned in many surgical series that routine IA for DAVF is recommended and is useful, there is no report specifically analyzing the role of IA in surgery for DAVF, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%